African Ministerial Conference of the Environment in Arusha, Tanzania - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
The 14th session of the African Ministerial Conference of the Environment (AMCEN) brought together Ministers from 40 countries. It was held at the Arusha International Conference Center (AICC) in Aursha, Tanzania, 10 - 14 September, 2012. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa Regional Office organized a successful side event during the conference. The CCAFS side event—entitled "Integrating Food Security and Sustainable Agriculture into Climate Change Polices"—was attended by more than 50 policy makers from 17 African and European countries. It was moderated by Yacob Mulugeta of the African Climate Policy Centre (ACPC).